2003
DOI: 10.1046/j.1523-1755.2003.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with ramipril attenuates renal osteopontin expression in diabetic rats

Abstract: Up-regulation of OPN expression may play a role in tubulointerstitial injury associated with diabetic nephropathy, and blockade of the RAS by ramipril may confer renoprotection by decreasing OPN expression in non-insulin-dependent diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 49 publications
4
44
0
Order By: Relevance
“…74 Several animal studies have shown that Ang-II upregulates OPN expression, whereas the blockade of Ang-II by using an ACE inhibitor, such as ramipril, suppresses inflammatory cytokine OPN expression. 75 Our data demonstrate that ramipril was associated with a modest 12% reduction in plasma OPN levels.…”
Section: Inflammation and Adhesionmentioning
confidence: 55%
“…74 Several animal studies have shown that Ang-II upregulates OPN expression, whereas the blockade of Ang-II by using an ACE inhibitor, such as ramipril, suppresses inflammatory cytokine OPN expression. 75 Our data demonstrate that ramipril was associated with a modest 12% reduction in plasma OPN levels.…”
Section: Inflammation and Adhesionmentioning
confidence: 55%
“…For many years, it has been well known that OPN is upregulated in the interstitium, especially the proximal tubules, in the diabetic kidney. [12][13][14] Moreover, OPN deficiency prevents the development of diabetic nephropathy in murine models. 19,20 We recently reported that a peroxisome proliferator-activated receptor d agonist, GW0742, attenuates diabetic nephropathy by suppressing inflammatory mediators, including OPN and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Because OPN is a macrophage chemotactic protein, OPN expression and macrophage accumulation may play a role in the tubulointerstitial injury in diabetic nephropathy in rats 13,14 and mice. 15,16 Moreover, we and others have shown by DNA microarray studies that OPN gene expression is upregulated in the renal cortex and correlated with the degree of albuminuria in diabetic nephropathy, [16][17][18] suggesting that regulation of OPN expression could be a potential target for therapeutic intervention in diabetic nephropathy.…”
mentioning
confidence: 99%
“…The severity of glomerular proliferation, interstitial fibrosis, and tubular proteinaceous cast scores were evaluated using light microscopy according to previously described methods (4,25,(33)(34)(35)(36)(37). Briefly, glomerular proliferative lesions were scored into five grades as follows: 0, no proliferation; 1, minor (segmental lesion Ͻ25%); 2, mild (segmental lesion Ͼ25% but Ͻ50%); 3, moderate (diffuse proliferation without severe sclerotic change); and 4, severe (diffuse proliferation with nearly complete sclerosis) (4,33,34,36).…”
Section: Histologic Examinationmentioning
confidence: 99%
“…A minimum of 40 glomeruli were examined in each PAS-stained specimen. The severity of tubulointerstitial fibrosis was assessed by counting the percentage of injured areas per field and then scored as follows: 0, normal interstitium; 0.5, Ͻ5% of areas injured; 1, 5 to 15%; 1.5, 16 to 25%; 2, 26 to 35%; 2.5, 36 to 45%; and 3, Ͼ45% (35,36). A minimum of 20 fields were evaluated for each Masson's trichromestained specimen.…”
Section: Histologic Examinationmentioning
confidence: 99%